Social Policy Trends: Poverty Reduction in Alberta vs. Ontario - Ronald Kneebone; Margarita Wilkins (The School of Public Policy Publications, 2023)
In 1976 and 2020, Alberta and Ontario had similar rates of poverty. In between those years, poverty rates followed very different trajectories.